2016
DOI: 10.3109/0886022x.2016.1148725
|View full text |Cite
|
Sign up to set email alerts
|

Lipoic acid does not improve renal function markers in 5/6 nephrectomy model: possible role of Nrf2 inactivation

Abstract: Chronic kidney disease (CKD) progression and complications are associated with increased oxidative stress, as well as with Nrf2 inactivation. Lipoic acid (LA) has been considered an inducer of Nrf2 antioxidant response. We tested whether oral administration of LA provides beneficial effects in experimental CKD in rats. Wistar rats underwent 5/6 nephrectomy (CKD group) or sham laparotomy. Seven days later, CKD group was divided into three subgroups that received: (i) LA continuously in the drinking water (100 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Another potential mechanism of ALA’s nephroprotection in diabetes is its ability to activate the Nrf2 signaling pathway, leading to upregulation of the second-phase cytoprotective proteins such as heme oxygenase-1 (HO-1) and NAD(P)H quinone dehydrogenase 1 (NQO1) [ 56 , 57 , 58 ]. It should be pointed out that while ALA is nephroprotective in diabetic kidney disease, it may impose pro-oxidant or toxic effects and could fail to serve as an Nrf2 inducer under certain pathophysiological conditions [ 59 , 60 , 61 ]. Additionally, while ALA has been thought to activate insulin signaling pathways to combat diabetes [ 28 ] and has been shown to prevent high fructose-induced cardiometabolic disorders and renal dysfunction [ 62 ], it has also been reported that ALA could only attenuate proteinuria and oxidative stress without slowing progression of diabetic renal failure [ 63 ].…”
Section: Protective Roles Of α-Lipoic Acid (Ala) In Kidney Injurymentioning
confidence: 99%
“…Another potential mechanism of ALA’s nephroprotection in diabetes is its ability to activate the Nrf2 signaling pathway, leading to upregulation of the second-phase cytoprotective proteins such as heme oxygenase-1 (HO-1) and NAD(P)H quinone dehydrogenase 1 (NQO1) [ 56 , 57 , 58 ]. It should be pointed out that while ALA is nephroprotective in diabetic kidney disease, it may impose pro-oxidant or toxic effects and could fail to serve as an Nrf2 inducer under certain pathophysiological conditions [ 59 , 60 , 61 ]. Additionally, while ALA has been thought to activate insulin signaling pathways to combat diabetes [ 28 ] and has been shown to prevent high fructose-induced cardiometabolic disorders and renal dysfunction [ 62 ], it has also been reported that ALA could only attenuate proteinuria and oxidative stress without slowing progression of diabetic renal failure [ 63 ].…”
Section: Protective Roles Of α-Lipoic Acid (Ala) In Kidney Injurymentioning
confidence: 99%